A Study of Guideline and Teaching for The Olympic Education in Thailand - Suriyan Somphong (Yayasan Keluarga Guru Mandiri, 2021)
The purposes of this study were to study the guidelines and teaching for the Olympic education that were to instil conscience of Olympic values. The 30 samples in this study were purposively sampled method. They were the experts from the National Olympic Committees of Thailand and Ministry of Education. The instruments were semi-structured interview developed by the researcher. The qualities of the instruments were verified by measuring the construct validity, calculating the index of congruence under the considerations of the experts, and determining the reliability with Cronbach’s method, respectively. The results of the research showed that the guidelines for teaching Olympic education in primary schools for cultivating Olympic values for students must create a network-based collaboration.